Protaeropsis, a new replacement generic name for fossil Sphenaster Jeffery, 1999 (Echinoidea: Spatangida) nec Wilcoxon, 1970 (Protista: Haptomonada) - Doweld, Alexander B. (Zootaxa, 2016)
The genus Sphenaster was erected by Jeffery (in Smith et al. 1999: 131) for a distinctive fossil echinoid of the Thanetian (Palaeocene) age from Spain and considered to be the most ancient element of the echinoid family Aeropsidae Clark, 1917 (Spatangida, Echinoidea). Unfortunately, up to now (Kroh 2010), it was not realized that the generic name Sphenaster is invalid, being a junior homonym of Sphenaster Wilcoxon, 1970: 80, a genus of fossil protist (Haptomonada).